Recognition of new States: An Analysis of selected Case Studies from a Third World Approach to International Law (TWAIL) - Seneviratne, Wasantha; Thilakarathna, K.A.A.N. (University of Colombo, 2021)
Despite progressive developments over the past, some areas of international law still require further improvements. Recognition of a new State is such an area, generally a decision by a recognizing State based on policy and politics than law, for which international law hardly provides an unbiased legal framework. The absence of such a non-politicized criterion to recognize new States necessitates to craft an appropriate legal yardstick as this lacuna shows the unavailability of a relevant treaty or a customary international law principle, notwithstanding the prevalence of the seemingly outmoded ‘Montevideo Convention on the Rights and Duties of a State of 1933’, which provides a criterion of Statehood to be satisfied by an entity as a pre-requite to be recognized as a State. States known as ‘third world countries’, particularly face frequent secessionist attempts due to complex religious and ethnic diversities in their territories, which pose threats to their sovereignty, political independence, and territorial integrity, and mostly are former colonies of the Western powers that may continue to be affected by their geo-politics. This research is to analyze the State practices pertaining to the recognition of States from a third world perspective on international law (TWAIL) with reference to selected case studies, namely, Kosovo, South Sudan, Crimea, and Catalonia, since they present legal issues associated with recognition of States. Findings of the research demonstrate a lack of uniformity in the State practices, coupled with the dearth of formal legal sources for the recognition of new States, which has had a potential to affect the third world countries adversely by making them persistent victims of the powerful countries of the West. Conclusion of the research highlights the need to craft a proper legal criterion, followed with a suitable mechanism, to protect the rights and interests of third world countries.
Keywords: Recognition of States; Third World Approach to International Law; Criteria for Statehood